Efektivitas Layanan Bimbingan Kelompok dengan Teknik Cognitive Restructuring untuk Meningkatkan Toleransi Beragama Siswa Kelas XI-8 SMA N 1 Mejobo Kudus - Maulana Wihartanty; Edris Zamroni; Indah Lestari (STKIP PGRI SUMENEP, 2025)
Religious tolerance is one of the important things that every person must have, because basically religious tolerance creates harmony, peace and tranquility in social life. This research was conducted to see the effectiveness of group guidance services using cognitive restructuring techniques in increasing religious tolerance in classes XI-8 SMA N 1 Mejobo Kudus. The population in this study was 36 students in class XI-8 and the subjects consisted of 8 students. This research method is a one group pre-test and post-test experiment with quantitative research. Before providing group guidance services using cognitive restructuring techniques, the average was 125 and after providing group guidance services using cognitive restructuring techniques, the average increased by 209.375 with a difference of 84.375%. The test results show that group guidance is effective in increasing students' religious tolerance where the asymp sig (2-tailed) value is 0.012, where 0.012 <0.05 so the hypothesis is accepted.